Aortic arch/elephant trunk procedure with SiennaTM graft and endovascular stenting of thoraco-abdominal aorta for treatment of complex chronic dissection - Wong, Randolph H.L.; Baghai, Max; Yu, Simon C.H.; Underwood, Malcolm J. (Annals of Cardiothoracic Surgery, 2013)
Aneurismal dilatation of the remaining thoracic aorta after ascending aortic interposition grafting for type ‘A’ aortic dissection is not uncommon. For such complex cases, one treatment option is total arch replacement and elephant trunk procedure with the SiennaTM collared graft (Vascutek, Inchinnan, UK) technique followed by a staged thoracic endovascular aortic repair (TEVAR). The video illustrates our technique in a 56-year-old man with an extensive aortic arch and descending thoracic aortic dissecting aneurysm. For the ‘open’ procedure femoral arterial and venous cannulation was used along with systemic cooling and circulatory arrest at 22 ℃. Upon circulatory arrest, the aortic arch was incised and antegrade cerebral perfusion achieved via selective cannulation to the right brachiocephalic and left common carotid artery, keeping flow rates at 10-15 mL/kg/min and perfusion pressure at 50-60 mmHg. Arch replacement with an elephant trunk component was then performed and after completion of the distal aortic anastomosis antegrade perfusion via a side-arm in the graft was started and the operation completed using a variation of the ‘sequential’ clamping technique to maximize cerebral perfusion. The second endovascular stage was performed two weeks after discharge. Two covered stents were landing from the elephant trunk to the distal descending thoracic aorta, to secure the distal landing a bare stent of was placed to cover the aorta just distal to the origin of the celiac axis. The left subclavian artery was embolised with fibre coils. Post TEVAR angiogram showed no endoleak Although re-operative total arch replacement and elephant trunk procedure and subsequent TEVAR remained a challenging procedure, we believe excellent surgical outcome can be achieved with carefully planned operative strategy.